Relationship between BMI, CT-derived body composition and colorectal neoplasia in a bowel screening population. Issue 3 (August 2022) - Di Rollo, Domenic G.; McGovern, Josh; Morton, Christopher; Miller, Gillian; Dolan, Ross; Horgan, Paul G.; McMillan, Donald C.; Mansouri, David
Introduction: Obesity is associated with an increased risk of colorectal cancer (CRC). Unlike the indirect measures such as BMI, CT-Body composition (CT-BC) allows for the assessment of both volume and distribution of adipose tissue. Therefore, the aim of this study was to examine the relationship between host characteristics, BMI, CT-BC measurements and the incidence of colorectal neoplasia. Methods: Patients undergoing CT Colonography (CTC) as part of the Scottish Bowel Screening Programme, between July 2009 and February 2016, were eligible for inclusion. Data were collected including demographic data, clinicopathological variables and CT-BC measurements including skeletal muscle index (SMI), subcutaneous fat index (SFI) and visceral fat area (VFA). CTC, colonoscopy, and pathology reports were used to identify CRC incidence. Associations between demographic data, clinicopathological variables, CT-BC measurements, colorectal neoplasia and advanced colorectal neoplasia were analysed using univariate and multivariate binary logistics regression. Results: 286 patients met the inclusion criteria. Neoplasia was detected in 105 (37%) of the patients with advanced neoplasia being detected in 72 (69%) of patients. On multivariate analysis sex (p < 0.05) and high VFA (p < 0.001) remained independently associated with colorectal neoplasia. On multivariate analysis a high SFI (p < 0.01) remained independently associated with advanced colorectal neoplasia. BMI was not associated with either colorectal neoplasia or advanced colorectal neoplasia. Conclusion: When directly compared to BMI, CT derived fat measurements were more closely associated with the degree of neoplasia in patients undergoing colorectal cancer screening. In patients investigated with CT colonography, CT adipose measures may stratify the risk and grade of neoplasia.